2011
DOI: 10.1108/02635571111170758
|View full text |Cite
|
Sign up to set email alerts
|

Quality management, strategic priorities and performance: the role of quality leadership

Abstract: Purpose -The purpose of this paper is to clarify whether there are differences in the implementation of quality management (QM) and the results achieved, based on the position of the person responsible for QM and his/her strategic priorities. Design/methodology/approach -Data from 256 firms that have implemented QM are collected. A multigroup analysis with LISREL is employed to contrast the hypotheses using a sample of general managers on the one hand and of quality managers on the other. Findings -This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 106 publications
(110 reference statements)
0
14
0
Order By: Relevance
“…Despite ambiguous empirical results, researchers continue to argue that research on strategic clarity requires grabbing-attention (Parnell, 2011;Albacete-Saez et al, 2011). Guth and MacMillan (1989) posit that perception of middle managers on strategic vision have an impact on their involvement in strategy implementation.…”
Section: Strategic Claritymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite ambiguous empirical results, researchers continue to argue that research on strategic clarity requires grabbing-attention (Parnell, 2011;Albacete-Saez et al, 2011). Guth and MacMillan (1989) posit that perception of middle managers on strategic vision have an impact on their involvement in strategy implementation.…”
Section: Strategic Claritymentioning
confidence: 99%
“…In line with the previous discussion, the first element of strategic clarity is 'aligned Dodi Permana 7 with vision'. An immense amount of attention has recently been focused on the advantages, particularly for organisations facing dynamic environments, of a compelling strategic vision (Andrews et al, 2012;Boyne et al, 2012;Albacete-Saez et al, 2011). In addition, Coulson-Thomas (1992) proposed that clarity of strategic vision is extremely significant in the implementation of organisational strategy.…”
Section: Theoretical Perspective and Hypothesis Developmentmentioning
confidence: 99%
“…Several studies contribute to a further understanding how factors such as context (e.g. Sousa & Voss, 2001), contingency (Sitkin, Sutcliffe & Schroeder, 1994;Sousa & Voss, 2008), infrastructure (Zu, 2009), firm size (Temtime, 2003), performance (Flynn, Schroeder & Sakakibara, 1994) and management and leadership (Albacete-Sáez, Fuentes-Fuentes & Bojica, 2011;Lakshman, 2006) link to quality management practice. Certainly, practices linked with specified roles in quality management have been addressed (e.g.…”
Section: Background and Research Problemmentioning
confidence: 99%
“…Accordingly, Bryson, (2018) emphasized that the organization that suffers from a lack of commitment, especially at the senior management level. Albacete-Sáez et al, (2011) [44] stated that the implementation of the organizational strategic priorities depends on the commitment of the top management. It was found that the employee and his contributions have an active role in the organizational strategic process, which leads to a greater understanding of the strategy among the staff and a greater commitment to the strategy [45]- [47].…”
Section: B Organizational Commitment and Organizational Performancementioning
confidence: 99%